Assessment of the applicability of goal- and risk-based design on Arctic sea transport systems. (1st December 2016) - Bergström, Martin; Erikstad, Stein Ove; Ehlers, Sören
Abstract: This paper proposes a framework for holistic goal- and risk-based design (GBD/RBD) of arctic maritime transport systems (AMTS). In order to best utilize the principles of GBD/RBD, the framework treats an AMTS as a hierarchy of subsystems. Each subsystem performs a specific function and can be designed separately. As a result, it possible to apply GBD/RBD where appropriate and feasible, and to use other methods where not. In addition, the applied system thinking makes it possible to extend the boundaries of the design process beyond the individual ship, making it possible to consider the performance of an AMTS as a whole. In order to assess the stochastic performance of an AMTS, and to produce the operational data required for the design of its individual ships, the framework integrates simulations and probabilistic assessments into the design process. To further extend the applicability of the framework, a number of knowledge gaps (e.g. an incomplete understanding of the ship-ice interaction), data gaps (e.g. a lack of full-scale ice load measurements), and regulatory gaps (e.g. a lack of performance measures and criteria for some ship functions) need to be addressed. Highlights: A framework for holistic goal- and risk-based design of arctic maritime transport systems is proposed. The proposed framework applies a systems-based approach extending the design boundaries beyond the individual ship. The framework supports a hybrid regulatory system including a combination of prescriptive, goal-, and risk-based rules. The integration of simulations and probabilistic assessments into the design process is advocated. Knowledge and regulatory gaps that need to be addressed to extend the applicability of the framework are identified.